2017
DOI: 10.1371/journal.pone.0182923
|View full text |Cite
|
Sign up to set email alerts
|

ERK2 and JNK1 contribute to TNF-α-induced IL-8 expression in synovial fibroblasts

Abstract: Tumor necrosis factor α (TNF-α) induces the expression and secretion of interleukin 8 (IL-8), which contributes to synovitis in rheumatoid arthritis (RA). To elucidate the mechanism of the onset of RA, we used synovial fibroblasts without autoimmune inflammatory diseases and investigated MAPK signaling pathways in TNF-α-induced IL-8 expression. Synovial fibroblasts isolated from healthy dogs were characterized by flow cytometry, which were positive for the fibroblast markers CD29, CD44, and CD90 but negative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 70 publications
(79 reference statements)
0
50
1
Order By: Relevance
“…p38 and JNK are members of the MAPK family and activated by environmental stress, including ultraviolet exposure, oxidative stress, or inflammatory cytokines 36 . They have been suggested to induce COX2 expression in inflammatory processes, such as rheumatoid arthritis or Parkinson's disease, and in human cancer-promoting inflammation [37][38][39] . Our results suggested that the p38/JNK pathway also regulates PGE2 production in cUC cells in a manner different from that of the RAF/MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…p38 and JNK are members of the MAPK family and activated by environmental stress, including ultraviolet exposure, oxidative stress, or inflammatory cytokines 36 . They have been suggested to induce COX2 expression in inflammatory processes, such as rheumatoid arthritis or Parkinson's disease, and in human cancer-promoting inflammation [37][38][39] . Our results suggested that the p38/JNK pathway also regulates PGE2 production in cUC cells in a manner different from that of the RAF/MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were harvested using 0.25% trypsin-EDTA once they reached 90-95% confluence. The collected cells were suspended in CELLBANKER 1 plus medium at a density of 2 × 10 6 cells/500 μL, and 500 μL of the cell suspension was placed into each sterilized serum tube as previously described [28][29][30][31][32][33][34][35]. The tubes were then placed in a freezing vessel (BICELL) and cryopreserved at −80˚C.…”
Section: Cell Cryopreservationmentioning
confidence: 99%
“…Western blotting was performed as previously reported [28][29][30][31][32][33][34][35]. The cells were lyzed using lysis buffer containing 20 mM HEPES, 1 mM PMSF, 10 mM sodium fluoride, and a complete mini EDTA-free protease inhibitor cocktail at pH 7.4.…”
Section: Western Blottingmentioning
confidence: 99%
See 2 more Smart Citations